Determinación de las propiedades físicas, caracterización química y evaluación de la actividad biológica del aceite esencial de hierba luisa (Cymbopogon citratus (DC) Stapf) - Astudillo Davila, Paola Thalia (2018)
Abstract: The essential oil of Cymbopogon citratus was isolated by steam-water distillation. The oil was characterized by physical tests that determined a density of 0.880 g/mL, refractive index of 1.477 and optical activity of -0.741 °. The volatile components present in the essential oil were studied using the gas chromatography technique coupled to mass spectrometry and the flame ionization detector. It was possible to recognize 21 compounds that represent 99.36% of the total identified. Major compounds were: geraniol (49.09%), geranial (17.82%), neral (12.49%), citronellal (6.92%), (Z) -Caryophyllene (3.6%) and citronellol (3.31%). The results obtained by the broth microdilution method showed that the essential oil presented moderate antimicrobial activity against Staphylococcus aureus, whereas against Escherichia coli, Enterococcus faecalis and Candida albicans showed weak activity, against Micrococcus luteus the oil was inactive. The antioxidant activity evaluated throught methods ABTS and DPPH shows that the essential oil is able to reduce 50% of the radicals with doses of 41.43 μg/mL (ABTS) and 146.26 μg/mL (DPPH) of essential oil.